Estimation of erythrocyte population state by the spherical index distribution - Gordiyenko, O.I.; Gordiyenko, Yu.E.; Makedonska, V.O. (Elsevier B.V., 2004)
The densities of cell distribution by spherical index (SI) in erythrocyte populations from healthy adults and donors with endocrine pathologies were determined via the developed method. The investigation shows that this characteristic varies for different donors, thereby reflecting the erythrocyte population state of an individual donor. Individual distribution curves obtained from healthy donors are close to Gaussian and are characterised by smooth curve plot with one maximum. Cells distribution by SI in donors with endocrine pathologies has a polymodal character. Our research shows that the developed method for determining erythrocyte distribution density by SI is a sensitive and informative test for quantitative evaluation of an erythrocyte population state. Moreover, this characteristic has clear physical and physiological significance, because an erythrocyte shape is strongly conditioned by the cell age and influences the ability to pass through microcapillaries in blood circulation.
Keywords: erythrocytes; Spherical index; Endocrine pathologies